The ABC's of getting out of debt - Sutton, Garrett; Time Warner AudioBooks (Firm) ([New York, N.Y.] : Time Warner Audiobooks, 2004)
Learn how to trade bad debt for good debt and maximize credit in this step-by-step guide. Get the details on the fastest ways to wipe out bad debt, as well as simple strategies to maximize one's credit rating. Whether trying to get out of debt, or making sure one's credit is in the best shape possible, readers will discover that this book can be worth thousands of dollars!
Produced and directed by Dennis Kao
Keywords: Consumer credit; Debt; Finance, Personal